Patient-reported distress can aid clinical decision-making in idiopathic pulmonary fibrosis: analysis of the PROFILE cohort. Issue 5 (9th May 2019) - Stewart, Iain; McKeever, Tricia; Braybrooke, Rebecca; Oballa, Eunice; Simpson, Juliet K.; Maher, Toby M.; Marshall, Richard P.; Lukey, Pauline T.; Fahy, William A.; Jenkins, Gisli; Saini, Gauri
Idiopathic pulmonary fibrosis is a progressive and fatal interstitial lung disease. We aimed to determine if patient response to a palliative assessment survey could predict disease progression or death. We undertook a cross-sectional study in a UK clinical cohort of incident cases. Rasch-based methodology provided a disease distress value from an abridged 11-item model of the original 45-item survey. Distress values were compared with measures of lung function. Disease progression or mortality alone was predicted at 12 months from survey completion, with risk of death assessed at 3, 6 and 12 months. Disease distress values were negatively correlated with lung function (r=−0.275 for the percentage predicted diffusing capacity of the lung for carbon monoxide). Expected survey scores computed from distress values could distinguish disease progression (n=8.8, p=0.004) and death (n=10.2, p=0.002) from no disease progression (n=6.9). Actual survey scores predicted disease progression and death with an area under the curve of 0.60 and 0.64, respectively. Each point increment in actual score increased risk of 12-month mortality by 10%; almost 43% of people scoring above 18 did not survive beyond 105 days. We define a short questionnaire that can score disease distress and predict prognosis, thus assisting clinical decision-making in progressive fibrosis. Responses to a palliative care survey from a clinical cohort of over 240 IPF patients were used to create a concise 11-item distress measure that can help predict disease prognosis with similar reliability to lung function recordings http://ow.ly/QCCt30nMEWU